Understanding Virtual Laboratories in Engineering Education: A Systematic Literature Review - Muhamad Nur Azmi Wahyudi; Cucuk Wawan Budiyanto; Indah Widiastuti; Puspanda Hatta; Mohd. Shafie bin Bakar (International Journal of Pedagogy and Teacher Education, 2023)
Engineering education has gained significant importance in the 21st century due to its integration of essential technological literacy needed in our rapidly changing world. Laboratories, including virtual laboratories, allowstudents to apply theoretical knowledge practically. Virtual laboratories have emerged as innovative tools that offer increased accessibility and flexibility. This study reviewed 29 peer-reviewed journal articles indexed in Scopus and published between 2018 and 2023 on the use of virtual laboratories in engineering education. The research employed a systematic literature review framework, utilizing PRISMA for article selection.The findings indicate that virtual laboratories provide numerous benefits, including cost-effectiveness, flexibility, safety, and accessibility. They boost student motivation, engagement, and the ability to apply knowledge while effectively enhancing conceptual understanding and practical skills. Virtual laboratories support the development of pedagogical skills and promote careers in engineering by offering a comprehensive and inclusive learning environment.Despite these advantages, challenges likelimited interactivity, restricted content, and technical issues persist. Virtual laboratories are valuable supplements to traditional laboratories, providing an economical means to explore phenomena and offering a safe space for experimentation. Educators should consider the benefits and limitations ofintegrating virtual laboratories into their curriculum. This study aims to deepen the understanding of virtual laboratories in engineering education, advocating for their broader adoption as an innovative tool with a positive impact.